THE SIBERIAN FOOD SUPPLIES: THE SOURSE OF ORGANIC FOOD EXPORTS TO SOUTH AND EAST ASIA MAKERS - Vasili , Kuimov; Suslova , Yu.Yu.; Shcherbenko ,; Yushkova , (Revista Inclusiones, 2020)
The article examines global food market problems with the focus on fighting hunger and meeting the growing demand for organic food products (OFP). The authors address the current situation, and study the prospects of resource development and the potential for organic food production in ecologically clean regions of Siberia and Krasnoyarsk Krai. New opportunities are presented for the development of OFP production in these regions in conditions of availability of land, water and forest areas. Special attention is devoted to wild plants as a valuable source of organic food. The growing markets of South and East Asia are seen as the most promising OFP export destinations.